2020
DOI: 10.31742/ijgpb.79.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity analysis and DNA fingerprinting of cotton varieties of India

Abstract: Genetic diversity was assessed in 48 popular varieties of tetraploid cotton from each cultivated zone of India using 68 SSR markers distributed across linkage groups. The markers produced a total of 144 alleles with an average of 2.19 per locus. The polymorphism information content (PIC) ranged from 0.04 to 0.57 with a mean of 0.23 indicating lesser diversity in the studied material. Jaccard’s similarity index based neighbourhood joining cluster analysis grouped the genotypes into three major clusters, each of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The higher polymorphism per cent observed in the present study might be due to inclusion of different species of cotton in the study. In our earlier diversity studies, 16 and 27 per cent SSR polymorphism was observed in G. arboreum (Santosh et al, 2020) and tetraploid cotton (Santhy et al, 2019), respectively. Earlier, Selvakumar et al (2010) observed 30 per cent polymorphism during genetic purity analysis of three cotton hybrids using SSR markers.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…The higher polymorphism per cent observed in the present study might be due to inclusion of different species of cotton in the study. In our earlier diversity studies, 16 and 27 per cent SSR polymorphism was observed in G. arboreum (Santosh et al, 2020) and tetraploid cotton (Santhy et al, 2019), respectively. Earlier, Selvakumar et al (2010) observed 30 per cent polymorphism during genetic purity analysis of three cotton hybrids using SSR markers.…”
Section: Resultsmentioning
confidence: 65%
“…The genetic similarity of 0.85 was noted between intra-hirsutum hybrid, CSHH243 and its male parent CSH 2013, and between intra-hirsutum hybrid, CSHH1862 and its female parent GMS 16A, and between GMS 16A and CB 33. The SSR markers were highly efficient in capturing both intra-species and inter-species diversity (Abd El-Moghny et al, 2017;Santhy et al, 2019;Santosh et al, 2020) as they revealed higher genetic diversity between different species and lesser diversity within species or between hybrids and their parents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, artificial selection for a few traits in cotton germplasm by traditional breeding methods has resulted in narrow genetic diversity among cotton varieties. Consequently, the relatively narrow genetic base restricts the progress of the cotton breeding ( Zhang et al., 2008 ; Saleem et al., 2020 ; Santhy et al., 2019 ; Zhang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%